Prevalence of fatigue reported by physiotherapists operating diathermy equipment for microwave - Maria das Graças Anguera; Reinaldo José Gianini (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
Objective: To Analyze the association between prevalence of fatigue referred by physical therapists and their occupational exposure to radiation emitted by therapeutic microwave diathermy equipment. Methods: A Cross-sectional study conducted in 193 physical therapists from four cities of the west of Paraná State, Brazil. A specified structured web questionnaire was applied for collecting data about microwave diathermy exposition and potential confounders, plus the Multidimensional Assessment of Fatigue (MAF). Statistical analysis included logistic regression and Student's t-test. Results: The prevalence of fatigue in the category exposed to microwave diathermy was higher (15.0%) than in non-exposed (2.9%). On multivariate logistic regression, a significant independent association between exposure to microwave diathermy and prevalence of fatigue was observed (odds ratio 4.93; 95% confidence interval 1.04 - 23.25; p = 0.04). The Student's t-test showed significant difference between the number of hours exposed to diathermy microwave, being 3,839.1 within physical therapists who referred fatigue and 497.6 within others (p = 0.004). Conclusion: The results demonstrate a significant and independent association between occupational exposure of physical therapists to radiation of microwave diathermy and prevalence of fatigue. Therefore, occupational safety guidelines aimed at these professionals as a prevention of possible adverse effects, as well as the replication of this study are suggested.